Poor brain growth in extremely preterm neonates long before the onset of autism spectrum disorder symptoms - Padilla, Nelly; Bölte, Sven (Cerebral cortex, 2017)
Preterm infants face an increased risk of autism spectrum disorder (ASD). The relationship between autism during childhood and early brain development remains unexplored. We studied 84 preterm children born at <27 weeks of gestation, who underwent neonatal magnetic resonance imaging (MRI) at term and were screened for ASD at 6.5 years. Full-scale intelligence quotient was measured and neonatal morbidities were recorded. Structural brain morphometric studies were performed in 33 infants with high-quality MRI and no evidence of focal brain lesions. Twenty-three (27.4%) of the children tested ASD positive and 61 (72.6%) tested ASD negative. The ASD-positive group had a significantly higher frequency of neonatal complications than the ASD-negative group. In the subgroup of 33 children, the ASD infants had reduced volumes in the temporal, occipital, insular, and limbic regions and in the brain areas involved in social/behavior and salience integration. This study shows that the neonatal MRI scans of extremely preterm children, subsequently diagnosed with ASD at 6.5 years, showed brain structural alterations, localized in the regions that play a key role in the core features of autism. Early detection of these structural alterations may allow the early identification and intervention of children at risk of ASD.